Pre-operative N-Acetyl Cysteine for Prevention of Atrial Fibrillation After CABG Surgery in Pakistan - Shah, Syed Ali Raza Ali; Hasan Kirmani, Syed Muzaffar; Hussain, Syed Aqeel; Khalil, Hafsa; Naqvi, Syeda Sarah; Zahra Kirmani, Syeda Khursand (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the effect of NAC in prevention of post-operative atrial fibrillation in patients undergoing CABG. Study Design: Quasi experimental study. Place and Duration of Study: Adult Cardiac Intensive Care Unit, Armed Forces Institute of Cardiology & National Institute of Heart Diseases (AFIC&NIHD) Rawalpindi during 6 months. Methodology: 146 patients of both gender undergoing elective CABG were included in the study, having age between 30-70 years. However, any patient with history of arrhythmia including AF, thyroid dysfunction, ejection fraction less than 25%, any valvular lesion, dilated left atrium, dilated left ventricle, dilated right atrium, dilated right ventricle or having right atrial tear during surgery were excluded from the study. By using non-probability consecutive sampling, patients were divided into two groups by using envelope method. One group was given standard treatment (control group) while other group was named as NAC group (experimental group). Data analysis was performed using SPSS version-23. Descriptive statistics were reported as Mean±SD. Categorical variables were reported as frequency and percentage. Chi square test and T-test was used to determine association between different variables. Results: A total of 146 patients with mean age 55.27±7.3 yrs. 127(87%) were male and 19(13%) were females. 28(19.2%) patients had atrial fibrillation while 11(7.5%) patients had ventricular premature contractions (VPC). There was no statistically significant difference between ages (p=0.784), gender (p=0.461), AF (p=0.207) and VPC (p=0.347). Out of 73 (50%) patients from each group; the mean age of NAC group was 55.41±7.3 yrs and of control group was 55.08±7.1 yrs (p=0.784). Gender wise distribution of NAC group had 8(11%) females and 65(89%) males while in control group 11(15%) females and 62(85%) were males. AF was found to be 11(15%) and 17(23.3%) in NAC and control group respectively. In NAC group, VPC was 4 (5.5%) and in control group it was 66 (90.4%). Conclusion: This study shows that NAC decreases the frequency of post-operative atrial fibrillation and ventricular premature contractions, but the decrease is statistically insignificant in Pakistani population. However, keeping in view other beneficial effects of NAC, we would recommend more studies on this subject in Pakistani population.